The Managerial Competence of School Principals in Improving the Quality of Secondary Education - Syarifah Nargis; Niswanto; Ismail; Ibrahim; Juli Firmansyah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
Improving student learning outcomes depends on teacher involvement in learning and the principal's good managerial competence in carrying out managerial functions in the school environment. This research aims to find information about the principal's plan to improve the quality of education in Banda Aceh City State Middle Schools and to describe the managerial function of school principals in enhancing the quality of education in Banda Aceh City State Middle Schools.This research uses a field research approach, namely research, where researchers go directly into the field to look for materials close to the truth. The study was conducted directly at State Middle Schools in Banda Aceh City, namely State Middle School 1 and State Middle School 12 in Banda Aceh City. The results of the research prove that the managerial competence possessed by school principals at SMPN 1 and SMPN 12 Banda Aceh City has so far been the basis or guide in the process of placing school principals, which is based on planning ability, organizing ability, ability to carry out school activities and ability to carry out supervision of every activity at school. School principals who have reliable managerial competence can influence progress in the educational environment, teacher performance, the effectiveness of school governance, and the achievement of better educational outcomes.